Chinese National Condition Based Power Dispatching Optimization in Microgrids. (14th March 2018) - Chen, Gang; Wang, Jian-Ming; Yuan, Xiao-Dong; Chen, Liang; Zhao, Lu-Jia; He, Yu-Ling
Abstract : This paper proposed a study on the power dispatching optimization in the microgrid aiming at Chinese national condition based on PSO algorithm. The whole work is on the basis of the weighted factor variation of the objective function due to different weather conditions. Three cases including the good contamination-diffusing weather condition, the smog weather condition, and the normal condition are considered, respectively. In the case of smog weather, the new energy generation and the battery system will be all out to use as less power as possible from the primary grid so that the pollution produced by coal consumption in the thermal power plants can be upmost reduced. However, in the case of perfect contamination-diffusing weather, the battery is not used to reserve its lifetime, while a large amount of exchanged power from the primary grid is used to obtain a most economic-efficient effect. In normal condition, the power dispatching is performed in a most balanced way considering not only the cost but also the environmental management. The case study in Suzhou Industrial Part confirms the effectiveness of the proposed method in this paper.